PERBEDAAN KEBERSIHAN GIGI DAN MULUT PADA IBU HAMIL TRIMESTER I DAN III DI PUSKESMAS BERUNTUNG BARU KABUPATEN BANJAR KALIMANTAN SELATAN TAHUN 2022 - resnawaty, sri; utami, Naning kisworo; rahmawati, ida (Poltekkes Kemenkes Banjarmasin, 2022)
Based on data from the monthly PWS (Local Area Monitoring) report at theLucky Baru Health Center from January to July 2022 the number of pregnant womenwas 199 people, there were 105 pregnant women in the first trimester, and 94 pregnantwomen in the third trimester, the results obtained were 85 pregnant women (42, 78%) ofthem have dental health problems.This study aims to determine and analyze differences in dental and oral hygiene inpregnant women in the first and third trimesters. The type of research used is analytic.This research approach uses cross sectional. The total sample is 70 pregnant womenwith 35 respondents in the first trimester, 35 respondents in the third trimester. Samplingwith total sampling.The results showed that in the first trimester the average OHI-S was 2.53, the thirdtrimester was 1.48. In the results of statistical tests with Independent t test analysis, itwas found that the mean difference (average difference) was 1.05, with the known t-count value of 4.608, the p value (probability value) of the test showed p = 0.000, so it issmaller than 0.05 or (p = 0.000 < 0.05).It can be concluded that there are differences in dental and oral hygiene for pregnantwomen in the first and third trimesters in area of the BeruntungBaru Health Center,Banjar Regency, South Kalimantan. It is recommended that there be counseling activitiesby health workers for behavioral changes in pregnant women in maintaining dental andoral hygiene.